Relationships of Clinical and Computed Tomography-Imaged Adiposity with Cognition in Middle-Aged and Older African Americans - Parker, Kirby G (J Gerontol A Biol Sci Med Sci, 2018)
BACKGROUND: Adiposity depots may differentially affect cognition. African Americans (AA) have higher rates of obesity and dementia but lower visceral adipose tissue (VAT) than whites, yet are underrepresented in studies of adiposity and cognition. Our study compared relations of cognitive function to clinical adiposity measures and computed tomography (CT)-imaged abdominal adiposity in AA. METHODS: CT-imaged subcutaneous adipose tissue (SAT) and VAT measurements were obtained in the AA cohort of the Genetic Epidemiology Network of Arteriopathy Study (N = 652, mean age 68 ± 8.4 years, 74% females, 59% obese, 82% hypertensive). Clinical adiposity measures included waist circumference (WC) and body mass index (BMI). Global cognition was operationalized as a global cognitive z-score generated from the average of four cognitive domain z-scores. Generalized estimating equations were used to examine cross-sectional associations between individual standardized adiposity measures and cognition, accounting for age, sex, education, smoking status, and familial clustering. A collective model was constructed including multiple supported adiposity measures and age-by-adiposity interactions. RESULTS: In the collective model, higher WC was associated with worse global cognition, β = −0.12 (95%CI: −0.21, −0.03); higher SAT was associated with better cognition, β = 0.09 (0.01, 0.18); higher BMI was associated with worse cognition at younger ages with attenuation at older ages (BMI-by-age-interaction p = .004). VAT was not significantly associated with global cognition, β = −0.03 (−0.07, 0.02). CONCLUSIONS: WC may be the simplest and most efficient measure of adiposity to assess with respect to cognition in clinical settings, although studies to determine mechanistic effects of subcutaneous and other adiposity depots on cognition are warranted.